Bisnis Vlogging dalam Industri Media Digital di Indonesia - Mahameruaji, Jimi Narotama; Puspitasari, Lilis; Rosfiantika, Evi; Rahmawan, Detta (Jurnal ILMU KOMUNIKASI, 2018)
This study explores the phenomenon of Vlogger as a new business in the digital media industry in Indonesia. Vlogger refer to social media users who regularly upload a variety of video content with various themes. We used case study to describe and analyze Youtube’s significant role in managing Vlogger communities, and also design support systems to make the communities growth and sustainable. We also explore Vlogger role as Online Influencer. This study is expected to be one of the references related to Vlogger phenomenon in the context of digital media studies in Indonesia.